Detailed Evaluation of Long-term Gamified Residential Demand Management System Field Implementation - Dashti, Negar; Zehir, M. Alparslan; Gul, Hakan; Batman, Alp; Bagriyanik, Mustafa; Ozdemir, Aydogan; Kucuk, Unal; Soares, Filipe Joel (IEEE, 2019)
Long-term, regular, grid-aware participants are one of the cornerstones of demand management activities that provide grid services. However, voluntary participation to demand management activities is still at low rates, while most customers are not sufficiently aware of the management potential of their flexible loads. Smart metering and data post-processing play a vital role in demand management programs to visualize consumption profiles, highlight flexibility potential and evaluate load management performance of customers. Additionally, gamification techniques can be employed to motivate users to achieve behavioral changes in their consumption profiles, providing financial and social incentives. Long-term field demonstrations and exploration of detailed evaluation metrics have been the main gaps in this area of study. This paper presents and discusses the results of a 13-month field demonstration of a gamified residential demand management platform. 4-month monitoring period is followed by a 9-month gamification period in four houses in Istanbul, Turkey.